Red round globe hot burning : a tale at the crossroads of commons and closure, of love and terror, of race and class, and of Kate and Ned Despard - Linebaugh, Peter (University of California Press, 2019)
"Red Round Globe Hot Burning tells the story of an Irish revolutionary, Edward Despard, and his wife, Catherine, an Afro-American abolitionist, in their efforts on both sides of the Atlantic to maintain the commons against attempts to enclose and privatize its land and resources. Their story takes the form of a quest, or two related searches for a woman and for the commons. The story begins in Ireland, joins them at first in Jamaica and then in central America, before returning to London and their final struggle on behalf of "the principles of freedom, of humanity, and of justice." He attempted to organize an insurrection, she succeeded in halting the construction of the panopticon. His defeat at the gallows and hers in anonymous exile were part of a turning point in the history of the earth and the commencement of the anthropocene"--Provided by publisher.